Use of Geospatial Techniques in Monitoring Urban Expansion and Land Use Change Analysis: A Case of Lahore, Pakistan - Muhammad Nasar-u-minAllah Bhalli ,; Abdul Ghaffar, (Journal of Basic & Applied Sciences, 2015)
Rapid urban expansion and resultant temporal land use changes have a profound effect on the city’s environment and its surroundings. Due to its significance, it is essential to evaluate the urban expansion patterns and land use change analysis of mega cities of the world. For land use change detection, multi-source & multi-temporal satellite images along with GIS & remote sensing (RS) techniques are significant aspects in analyzing urban expansion all over the world. In present study, two image data sets of the Landsat system in 7/ETM+ and 8/OLI modes, along with ground truthing data were utilized to examine the spatio-temporal dynamics of land use changes and assess the spatial patterns of urban expansion in Lahore, Pakistan from the year 2000 & 2014. Supervised classification using maximum likelihood algorithm has been carried out for land use classification andPost classification change detection technique was used to produce change detection map of the study area. The output land use and change detection map revealed that the areal expansion has been attributed due to loss of agricultural land and urban sprawl while major change in land use has taken place in built-up and agricultural areas. The results indicated that 40.81% of built-up area increased, while agricultural land has decline by -12.98% during the study period (2000-2014). Due to this the observed expansion of the city has been toward the South-east, South and South-west along with major roads. The results infer can provide better understanding and information about the past and current spatial dynamics of land use change in Lahore, Pakistan.